Simultaneous adsorption and degradation of organic dyes using recyclable magnetic cucurbituril nanocomposite. (2021) - Trivedi, Maitrayee U.; Kanth P., Chandra; Pandey, Manoj Kumar
Abstract: Simultaneous adsorption and degradation of organic dyes from wastewater by one material offers a substantial advantage when fast, facile, and robust wastewater purification is essential. Herein, we present a cucurbituril capped magnetic nanoparticles intercalated montmorillonite as a highly recyclable dual-functional nanocomposite. Iron (II, III) oxide nanoparticles are synthesised using simple co-precipitation method and capped with cucurbit[6]uril followed by intercalation into pre-exfoliated montmorillonite lamella. The morphology and crystallite phase of Iron (II, III) oxide nanoparticles were investigated by FE-SEM and XRD. FTIR and DR-UV spectroscopy was used to examine the functional groups and composition of the cucurbituril capped nanoparticles before and after intercalation into montmorillonite clay. Each component in the nanocomposite owes definite importance towards pollutant removal from wastewater. The magnetic nanoparticles offer facile recovery and induce catalytic function for fenton like activity. Cucurbituril plays a dual role by acting as a binder between nanoparticles and montmorillonite to stabilise the nanocomposite and act as functional adsorbent. Montmorillonite is a versatile adsorbent and good solid support for nanoparticle immobilisation which improves pollutant-catalytic site interface. The synergetic effect between components in the nanocomposite is found to be very effective for wastewater treatment. The nanocomposite activity has been investigated for the treatment of dye contaminated water by fenton reaction and also by adsorption.